Covariant quantization of the superstring - Berkovits, Nathan [UNESP] (Elsevier, 2004)
After constructing a BRST operator from the fermionic Green-Schwarz constraints and a bosonic pure spinor ghost variable, the superstring is covariantly quantized and N-point tree amplitudes are computed in a manifestly ten-dimensional super-Poincaré covariant manner. © 2004 Published by Elsevier B.V.